The Cost of Contralateral Prophylactic Mastectomy in Women with Unilateral Breast Cancer. Issue 5 (May 2018) - Billig, Jessica I.; Duncan, Anthony; Zhong, Lin; Aliu, Oluseyi; Sears, Erika D.; Chung, Kevin C.; Momoh, Adeyiza O.
Abstract : Background: Contralateral prophylactic mastectomy may be unnecessary from an oncologic perspective; therefore, the debate persists about the value of contralateral prophylactic mastectomy in women with early-stage unilateral breast cancer. Given finite health care resources, this study aims to evaluate the cost of contralateral prophylactic mastectomy and breast reconstruction. Methods: Women with unilateral breast cancer undergoing either unilateral mastectomy or unilateral mastectomy with contralateral prophylactic mastectomy and immediate breast reconstruction were selected from the Truven MarketScan databases between 2009 and 2013. Demographic and treatment data were recorded, and over an 18-month follow-up period, the treatment cost was tallied. A log-transformed linear model was used to compare cost between the groups. Results: A total of 2343 women were identified who met our inclusion criteria, with 1295 undergoing unilateral mastectomy and 1048 undergoing contralateral prophylactic mastectomy. Complication rates within 18 months were similar for women undergoing unilateral mastectomy and contralateral prophylactic mastectomy (39 percent versus 42 percent; p = 0.17). Management with unilateral mastectomy with reconstruction required an adjusted cumulative mean cost of $33, 557. Contralateral prophylactic mastectomy with reconstruction was an additional $11, 872 in expenditure ( p < 0.001). The cost of initial procedures (mean difference, $6467) and secondary procedures (mean difference, $2455) were the greatest contributors to cost. Conclusions: In women with unilateral breast cancer, contralateral prophylactic mastectomy with reconstruction is more costly. The increased monetary cost of contralateral prophylactic mastectomy may be offset by improved quality of life. However, this financial reality is an important consideration when ongoing efforts toward reimbursement reform may not pay for contralateral prophylactic mastectomy if outcomes data are not presented to justify this procedure. Abstract : Supplemental Digital Content is available in the text.This and Related "classic" articles appear On prsjournal.com for Journal Club Discussions.